Kedisiplinan Sebagai Faktor Penunjang Karakter Siswa Kelas XI MAS Aisyiyah Di Sekolah Menengah Atas - Amini, Humairoh (EL-EMIR Institute, 2025)
Discipline is one of the fundamental factors in supporting the development of students' character, especially at the eleventh-grade level of Senior High School (SMA), where students are in a crucial phase of emotional and social development. This article aims to explore in depth the role of discipline in shaping students' character using a qualitative approach. Data collection techniques were carried out through direct observation, in-depth interviews, and documentation involving students and teachers at a selected high school. The research findings indicate that discipline plays a significant role in fostering positive values such as responsibility, honesty, maturity, and self-control. However, the success of implementing discipline is highly influenced by external factors such as the active involvement of teachers, parental support, and a school culture that reinforces positive behavior. Consistency in rule enforcement, exemplary conduct by educators, and a humane approach are key elements in strengthening students' character comprehensively and sustainably within the formal education environment.